The study of planting of non-ringed cuttings of hybrid mulberry in the conditions of the Tashkent region (Texas Journal of Agriculture and Biological Sciences, 2022)
In Tashkent region, the possibility of growing seedlings studied of hybrid mulberry varieties from uncut cuttings. The cuttings were prepared in the second decade of February and stored in trenches 50-60 cm deep before transplanting. Cuttings were carried out in two ways. The first method - horizontal 30–40 cm cuttings buried in the soil, placing them in a row on the edges of the furrow to a depth of 7–8 cm. The second oblique method - cuttings 20–25 cm in length are left on the soil surface. Horizontal cuttings have a higher root rate than those obliquely planted